2020
DOI: 10.1101/2020.11.17.20231548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of the SARS-CoV-2 serial interval and the impact of parameter uncertainty on the COVID-19 reproduction number

Abstract: The serial interval of an infectious disease, commonly interpreted as the time between onset of symptoms in sequentially infected individuals within a chain of transmission, is a key epidemiological quantity involved in estimating the reproduction number. The serial interval is closely related to other key quantities, including the incubation period, the generation interval (the time between sequential infections) and time delays between infection and the observations associated with monitoring an outbreak suc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…This corresponds with two other studies [30,31], but is lower than in a systematic review [32]. The serial interval is also dependent on the effectiveness of interventions, such as timing of isolation, and thus, may be changing over time [32,33]. The mean serial interval is almost one day shorter than the mean overall incubation period (4.6 days) but equal to the mean incubation period for cases coming from Austria (3.7 days).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This corresponds with two other studies [30,31], but is lower than in a systematic review [32]. The serial interval is also dependent on the effectiveness of interventions, such as timing of isolation, and thus, may be changing over time [32,33]. The mean serial interval is almost one day shorter than the mean overall incubation period (4.6 days) but equal to the mean incubation period for cases coming from Austria (3.7 days).…”
Section: Discussionsupporting
confidence: 70%
“…Out of 53 pairs of index and secondary cases, we estimated a mean serial interval of 3.9 days. This corresponds with two other studies [30,31], but is lower than in a systematic review [32]. The serial interval is also dependent on the effectiveness of interventions, such as timing of isolation, and thus, may be changing over time [32,33].…”
Section: Discussionsupporting
confidence: 59%
“…The characteristics and outcomes of patients infected with VOC B.1.1.7 are not yet known. Early analyses, of mortality linked to diagnostic data, have suggested that infection with VOC B.1.1.7 may be associated with a higher risk of mortality compared with infection with other virus variants 7,8,9,10,11,12 . However, these analyses had either limited adjustment for key patient characteristics thought to be associated with COVID-19 outcomes, or did not consider effects on critical care admission or outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the increase in mortality during the second half of 2020 was caused by mutations of the SARS-CoV-2 virus. The SARS-CoV-2 virus variant of concern (B.1.1.7), which was first detected in the United Kingdom has been associated with an enhanced mortality among out-patients with SARS-CoV-2 infection [19,20]. However, as virus variants of concern occurred only sporadically in Sweden before January 2021 [21], they were most likely not involved in the increased second wave mortality that was noted in this study.…”
Section: Discussionmentioning
confidence: 82%